Deutschlernen durch bewegliche Bilder? Zum Einsatz audiovisueller Medien im Sekundarbereich II in der Slowakei aus der Perspektive der Lehrenden - Michaela Kováčová; Veronika Jurková (Acta Facultatis Philosophicae Universitatis Ostraviensis. Studia Germanistica, 2022)
Movies are an essential part of our media reception. They have been used as a tool for learning foreign languages from the very beginning, but this trend has been growing in recent years. This quantitative study explores the attitudes of teachers from secondary schools in Slovakia to the use of audio-visual media as teaching material, and surveys how they apply AV material in German language lessons. A total 109 teachers participated in the survey, conducted in 2018–2020. The findings indicate that mostly short audio-visual formats, primarily educational videos, are integrated into German lessons at secondary schools, and that teachers usually apply tasks that are familiar from reading and listening activities. Creative interpretative methods are not given enough space.